Business Cycle Downturn Likelihood Estimation for Ciudad Juarez - Fullerton, Steven L.; Fullerton, Jr., Thomas M. (Journal of Applied Business and Economics, 2023)
A monthly frequency metropolitan business cycle downturn likelihood equation is estimated for Ciudad Juarez. The binary index of economic conditions is based upon monthly IMMEX export oriented manufacturing employment. A dynamic probit methodology is used for parameter estimation. Continuous explanatory variables include a 1-year minus 1-month Mexico interest rate spread, a 2015 = 100 weighted real exchange rate index, and a 10-year minus 3-month USA interest rate spread. Parameter estimation results confirm the various hypotheses examined. However, model simulation outcomes are less favorable with the results indicating that accurate forecasting of the post-2010 business cycles may require additional refinement to the index.